1971
DOI: 10.1017/s0043174500048256
|View full text |Cite
|
Sign up to set email alerts
|

Germination and Herbicide Susceptibility of Six Pigweed Species

Abstract: The germination and growth of six pigweeds (Amaranthus spp.) were studied in the germinator and greenhouse. Treatments with sulfuric acid, acetone, sodium hypochlorate, and potassium nitrate variously influenced species germination. Seedlings emerged more rapidly at 100 F than at other soil temperatures. Variation in seedling characteristics was noted. Some species were more susceptible to 4-(methylsulfonyl)-2,6-dinitro-N,N-dipropylaniline (nitralin) and 2,4-bis (isopropylamino)-6-(methylthio)-s-triazine (prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1975
1975
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Other studies have demonstrated that several Amaranthus spp. have a similar pattern of emergence due to limited carbohydrate reserves of these small seeded broadleaf weeds (Ghorbani et al 1999;Santelmann and Evetts 1971;Thomas et al 2006). Another possible explanation for lack of emergence from deeply buried seeds could be absence of light, hypoxia, and low rates of gaseous diffusion at deeper depths (Benvenuti 2003;Woolley and Stoller 1978).…”
Section: Naclmentioning
confidence: 99%
“…Other studies have demonstrated that several Amaranthus spp. have a similar pattern of emergence due to limited carbohydrate reserves of these small seeded broadleaf weeds (Ghorbani et al 1999;Santelmann and Evetts 1971;Thomas et al 2006). Another possible explanation for lack of emergence from deeply buried seeds could be absence of light, hypoxia, and low rates of gaseous diffusion at deeper depths (Benvenuti 2003;Woolley and Stoller 1978).…”
Section: Naclmentioning
confidence: 99%
“…Seedling treatment with herbicides that are generally considered ineffective for control of tall morningglory have reduced the elongation of primary roots over 50%, and have reduced the development of lateral roots (9). Growth responses of other weeds have indicated that stem absorption of herbicides applied preemergence can be equivalent to, or greater than root absorption depending upon the particular herbicide and weed species involved (6,8).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for the importance of seed germination responses in A. retrojexus is demonstrated by the many studies on this topic with this species (McWilliams 1965;Barton 1967;Wiese and Davis 1967;Andersen 1968;Taylorson and Hendricks 1969;Santelman and Evetts 1971). Hence the timing of seed germination can be the fundamental factor determining the success or failure of a young seedling or the ability of the mature plant to set viable seeds before the end of the growing season.…”
Section: Introductionmentioning
confidence: 99%